The efficacy, bioavailability and safety of a novel hydroalcoholic testosterone gel 2% in hypogonadal men: results from phase II open‐label studies. (24th November 2015) - Efros, M.; Carrara, D.; Neijber, A.
Summary: Pharmacokinetics, pharmacodynamics and safety of a novel hydroalcoholic testosterone gel 2% (TG) were evaluated in phase II sequential dose escalation studies using 3 application sites (thigh, abdomen and shoulder/upper arm) and 2 application methods. Hypogonadal men ( n  = 40), 18–75 years, with serum testosterone <300 ng dl −1 were included in both studies. Study 1 evaluated hand‐applied multiple doses of TG 1.25, 2.50 and 3.75 ml (23, 46 and 70 mg of testosterone, respectively), once daily for 10 days to shoulder/upper arm. Study 2 evaluated applicator‐applied (TG 1.25, 2.50 and 3.75 ml) versus hand‐applied (TG 2.5 ml) doses, once daily for 7 days to shoulder/upper arm. Primary endpoint for both studies was responder rate (Cave testosterone levels between 298 and 1050 ng dl −1 ). In Study 1 following multiple applications, >70% participants in each group were responders. Dose‐dependent increase was observed in PK values for total testosterone, free testosterone and DHT. In Study 2, responder rate was dose proportional: 16.7%, 50.0% and 77.8% responders in TG 1.25, 2.50 and 3.75 ml groups respectively. The bioavailability was highest for the shoulder application. There was a significant improvement in almost all the domains of sexual functioning. Applicator‐application was preferred over hand‐application by majority of the participants. TG was found to be safe and well tolerated in hypogonadal men.